SEX DETERMINATION AND GONAD DEVELOPMENT OF A MANGROVE PROSOBRANCH Tympanotonus fuscatus var fuscatus (LINNAEUS, 1758) FROM BONNY ESTUARY, NIGERIA - JAMABO, N. A; CHINDAH, A. C. (Nigerian Journal of Fisheries, 2011)
The sex determination/ratio and gonad development of Tympanotonus fuscatus var fuscatus in the mangrove swamps of Bonny River was studied for a period of twenty four months. Females were found to be dominant to males in the observed population. The trend was observed for the entire population as well as in the different seasons. Sex ratios however varied with season and maturity stages. T. fuscatus var fuscatus breeds between October and January. The non - productive season starts in February and continues till June. The breeding period which is restricted to October and January was attributed to increase in salinity and the flow of water current experienced in the dry season. Environmental factors and internal mechanism influences the initiation of gametogenesis of T. fuscatus var fuscatus. The study showed that temperature was not a controlling factor in the gonad development of T. fuscatus var fuscatus.